An Analysis Acceptance of Hospital Management Information Systems Using Technology Acceptance Model at Hospital Harapan Bunda Batam - Depi Yunaspi; Ermi Girsang; Sri Lestari Nasution; Tan Suyono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The hospital is one of the health care facilities by empowering various units of trained and educated personnel in dealing with and dealing with medical problems for the recovery and maintenance of good health (Setyawan D, 2016). From the explanation above about the definition of a hospital, it can be concluded that the hospital performs several types of services including medical services, medical support services, nursing services, rehabilitation services, prevention and health improvement, as a place for education and/or medical and medical training, as a place of research and the development of science and technology in the health sector as well as to avoid health risks and disturbances as intended, so it is necessary to carry out hospital environmental health in accordance with health requirements. This paper described a hospitals, which are part of the facilities that provide health services, are currently facing increasingly fierce competition, so hospitals must continue to strive to improve the quality of services offered to the community. Hospital competition conditions have a positive impact, namely providing more choices for the community. Efforts to improve service quality are efforts to improve the efficiency and effectiveness of organizational management as well as efforts to satisfy community needs. These efforts were carried out in all fields including the procurement of Hospital Management Information System (SIMRS).(Putra & Vadriasmi, 2020).